Indices of change in exposure and response prevention for contamination-based OCD. (October 2020) - Mathes, Brittany M.; Day, Taylor N.; Wilver, Natalie L.; Redden, Sarah A.; Cougle, Jesse R.
Abstract: Few studies have examined indices of change in treatment for obsessive compulsive disorder (OCD). The current study evaluated within- and between-session trajectories of fear, disgust, and urge to wash in exposure and response prevention (ERP) for contamination-based OCD and tested whether change in these indices were associated with treatment outcomes. Forty-one participants (75.6% female) engaged in three sessions of ERP for contamination OCD. Participants provided ratings of fear, disgust, and urge to wash during each session, and contamination symptoms were assessed at pre- and post-treatment and two-week follow-up. Fear, disgust, and urge to wash all significantly decreased both within and between sessions. Both fear and disgust declined significantly faster than urge to wash within session, though declines in fear and disgust did not significantly differ from each other. Within-session changes in fear were significantly associated with reduced symptoms at post-treatment, whereas within-session changes in disgust were associated with symptoms at two-week follow-up. The current study highlights the roles of fear and disgust in the context of ERP as unique indicators of treatment outcome for contamination-based OCD. Only within-session fear was uniquely associated with treatment outcome at post, while within-session disgust predicted outcome at follow-up. Theoretical and clinical implications are discussed. Highlights: Indices of change in exposure and response prevention were investigated. Fear and disgust reduced faster than urge to wash within treatment sessions. No differences in rates of decline were observed between sessions. Within-session changes in fear and disgust predicted symptom reduction.